President’s Message - Frenette, Karen; Khotar, Rupinder (Operating Room Nurses Association of Canada Journal, 2013)
This is the last message I will write as President of the Operating Room Nurses Association of Canada (ORNAC). Two years have passed so quickly. This has been a time of planning as ORNAC sets the groundwork for change. This change was necessitated by revisions to Industry Canada’s Not for Profit Act as well as challenges facing ORNAC and healthcare as a whole.